Overweight and Obesity and its associated factors among high school students of Dibrugarh, Assam, India - Gupta, Ekta; Mahanta, Tulika Goswami (Indian Journal of Community Health, 2016)
Background: The increasing prevalence of childhood obesity is emerging as a public health problem in urban India and also contributes to obesity and various non-communicable diseases among adult population. Hence, it is necessary to identify potential risk factors for childhood obesity and formulate early interventions to control this epidemic. Aims & Objectives: To assess the magnitude of overweight and obesity among high-school students of Dibrugarh and to determine factors associated with it. Materials & Methods: A cross-sectional study including students enrolled in 8th- 10th grades in schools of urban Dibrugarh, Assam was conducted from October 2012 to June 2013 wherein 1000 students were selected using stratified random sampling technique. Information regarding dietary intake, amount of physical activity was collected using pre-designed, pre-tested questionnaire followed by anthropometric measurements which included body mass index (BMI), waist and hip circumference was done. Statistical analysis was carried out using SPSS-16 software. Results: Of the 1000 students enrolled, 119 (11.9%) were overweight, 71 (7.1%) were obese and 225 (22.5%) had high waist-hip ratio. The factors significantly associated with overweight and obesity were higher socio-economic class, frequent intake of fast food items, sedentary lifestyle with less physical activity. Conclusion: Children belonging to higher socio-economic group, consuming fast food and involved in less physical activity were more predisposed to overweight and obesity.